The influence of perceived maternal rejection, perceived paternal rejection and father involvement on young women's psychological adjustment and depression - Avaz, Sena (İstanbul Bilgi Üniversitesi, 2011)
Kişilerarası ilişkiler bireylerin psikolojik işlevi ve gelişimi anlamında önem taşımaktadır. Kişilerarası ilişkiler dikkate alındığında, ebeveyn-çocuk ilişkisi en önemli olanıdır. Ebeveynlerin çocuklarına karşı tutumunun, çocuğun psikolojik uyumuna hayatı boyunca etkisi olabilmektedir. Anne ve babadan gelen sıcaklık ve sevgi, bireylerin psikolojik uyumunu güçlendirmektedir. Bu çalışmanın amacı, algılanmış anne reddi, baba reddi ve baba katılımının genç yetişkin kadınların psikolojik uyumu ve depresyonu ile ilişkisini incelemektir. Yaşları 19 ile 26 arasında dağılan 122 kadın, İstanbul Bilgi Üniversitesi'nden seçilmiştir. Algılanmış anne reddi, baba reddi ve baba katılımının genç yetişkin kadınların psikolojik uyumu ve depresyonu üzerindeki etkisini değerlendirmek amacıyla korelasyon ve regresyon analizleri yürütülmüştür. Sonuçlar, yalnızca algılanmış anne ve baba reddinin genç yetişkin kadınların psikolojik uyumu ve depresyonu ile ilişkisinin olduğunu göstermiştir. Algılanmış anne reddinin, baba reddine oranla daha etkili olduğu bulunmuştur. Bunun yanı sıra, algılanan baba katılımının, genç yetişkin kadınların psikolojik uyumu ve depresyonu ile bir ilişkisinin olmadığı bulunmuştur. Bu çalışma, algılanan ebeveyn reddinin, psikolojik uyum ve depresyon üzerindeki etkisine dair bir fikir sağlamaktadır.

Interpersonal relationships are important for individuals psychological functioning and development. When personal relationships are taken into consideration, parent-child relationship is the most important one among the others. Parental attitudes toward the child may have an impact on the childs psychological adjustment throughout her life. Warmth and affection from both mother and father may promote positive adjustment in individuals. The purpose of the present study was to investigate the relationship of perceived maternal rejection, perceived paternal rejection and father involvement with young women?s psychological adjustment and depression. 122 female students whose ages ranged from 19 to 26 (M= 21.09, SD=1.34) were selected from Istanbul Bilgi University as subjects. Correlation analyses and regression analyses were conducted to evaluate the influence of perceived maternal rejection, perceived paternal rejection and father involvement on young women?s psychological adjustment and depression. The results indicated that only perceived maternal and perceived paternal rejection were found to be significant contributors to young womens psychological adjustment and depression. Perceived maternal rejection was found to be more influential than perceived paternal rejection. However, perceived father involvement was found to be not significant to young womens psychological adjustment and depression. This study provides some insight into the impact of perceived parental rejection on young womens psychological adjustment and depression.
Algılanan anne reddi, baba reddi ve baba katılımının genç yetişkin kadınların psikolojik uyumu ve depresyonu üzerindeki etkisi